ZIKA VIRUS: A BRIEF REVIEW - AL-TAMEEMI, KANAAN; KABAKLI, RAIAAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
This review highlights the Zika virus which is considered a global concern due to its rapid pandemic potential and effect on humans, and according to its pandemic status, the World Health Organization declared on February 2016 it as a “Public Health Emergency of International Concern.” Therefore, we define the epidemiology of Zika virus in addition to its pathogenesis, diagnostic techniques, and treatment.